Driving Sustainable Performance of Banks through CSR, Green HRM, and Green Banking Practices: Mediation of Employee Green Behavior and Moderation of FinTech Adoption - Ashfaq, Muhammad; Akhtar, Shamim; Ullah, Kafait (Indonesian Journal of Sustainability Accounting and Management, 2026)
This research explores the effect of green human resource management practices, CSR activities, and green banking practices on the sustainable performance of banks in developing economies, with employee green behavior as a mediator and financial technology adoption as a moderator. Data were gathered for the study from 620 branch managers in the banking sector using self-administered printed and online questionnaires. We applied partial least squares structural equation modelling (PLS-SEM) to examine direct and indirect associations among the variables, and the results indicated that green banking practices significantly impact banks’ sustainable performance. Moreover, it was discovered that FinTech partially moderates the relationship between green banking practices and sustainable performance, and the adoption of GHRM practices and CSR activities improves banks’ sustainable performance. This study stands out by looking at the combined effects of green human resource management practices, CSR initiatives, and green banking practices on sustainability. This area has not received much attention in previous studies. It emphasizes how crucial employee green behavior and FinTech adoption are to maximizing banks’ sustainable performance. Furthermore, this study invoked the Social Exchange Theory, Resource-Based View, AMO Theory, Stakeholder Theory, and Institutional Theory to examine the relationship of study variables. Prominently, this research strengthens the 2030 Plan of the United Nations for Sustainable Development, particularly in relation to SDG 8, SDG 9, and SDG 13.